2021
DOI: 10.3390/ejihpe11030049
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Socio-Emotional Competencies and the Overlap of Bullying and Cyberbullying Behaviors in Primary School Students

Abstract: Digital life forms part of daily reality for young people. For this reason, traditional bullying in school has been reproduced in the online environment, resulting in an overlap of off- and online bullying. Research on socio-emotional competencies and bullying is revealing interesting results among students in secondary schools. However, studies involving primary school students are much scarcer. In addition, the majority of studies have been carried out based on an understanding of socio-emotional competencie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 63 publications
2
17
0
2
Order By: Relevance
“…These include cognitive, psychological, social, cultural, and societal factors [21]. Researchers have found that adolescents find it more difficult to control impulsive behaviors if they are with their peers or if high emotions are involved [22]. Examples include delinquent behavior in peer groups and at-risk behavior caused by decreased emotion regulation abilities [23].…”
Section: A Adolescent Identity Development and Social Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…These include cognitive, psychological, social, cultural, and societal factors [21]. Researchers have found that adolescents find it more difficult to control impulsive behaviors if they are with their peers or if high emotions are involved [22]. Examples include delinquent behavior in peer groups and at-risk behavior caused by decreased emotion regulation abilities [23].…”
Section: A Adolescent Identity Development and Social Mediamentioning
confidence: 99%
“…Cyberbullying is the intentional use of digital media to spread inaccurate, humiliating, or hostile information about another individual [41]. It is the most prevalent peer-to-peer internet danger for adolescents [22]. Although "online harassment" is frequently used interchangeably with "cyberbullying," it is a distinct phenomenon [42,43].…”
Section: Online Bullying and Cyberbullyingmentioning
confidence: 99%
“…Cyber-aggressors use the technology as a way to relieve their frustrations and generally have low self-esteem, problems expressing their emotions appropriately, and problems at school (Livazovic & Ham, 2019). The victims of cyberbullying intentionally harmed by the aggressor are usually introverted and timid, lacking social skills and social adaptation (Rodríguez-Álvarez et al, 2021). The lack of physical contact and unknown identity of the aggressor generate a feeling of desperation and helplessness in the victim that is worsened by the ease with which the harmful content quickly goes viral (Dong, 2020).…”
mentioning
confidence: 99%
“…On the one hand, the Italian study was conducted with Sicilian primary school students to examine the predictive capacity of sociodemographic variables (gender and age) and mechanisms of moral disengagement (moral justification, euphemistic language, advantageous comparison, displacement of responsibility, disclosure of responsibility, distorted consequences, blame attribution, and dehumanization) on the manifestation of three different roles that are characteristic of school violence: victims, aggressors, and bystanders [ 4 ]. On the other hand, the Spanish work was carried out with Spanish primary school students to analyze whether socio-emotional competencies (relationship skills, self-management, and social awareness) can affect the overlap of off- and online bullying in those who manifest the role of victims and to examine their gender differences [ 5 ]. The results of these works reveal that European children who suffer victimization tend to use moral justification and show low self-management, in the case of girls, and poor relationship skills, in the case of boys.…”
mentioning
confidence: 99%
“…Several practical implications are offered by this Special Issue to improve mental health and interpersonal relationships throughout the three evolutionary stages examined. During childhood and adolescence, authors suggest applying programs centered on the development of empathy and inter- and intrapersonal emotional intelligence to prevent both bullying and cyberbullying or to reduce their impact on students’ wellbeing [ 4 , 5 ]. According to Garaigordobil [ 6 ] and Doumas and Midgett [ 7 ], psychopathological symptoms are specially worrying in adolescents, so it is recommended that interventions targeting learners of secondary education include strategies to manage, for example, depression and anxiety.…”
mentioning
confidence: 99%